If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12x + -12 = 0 Reorder the terms: -12 + 12x = 0 Solving -12 + 12x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '12' to each side of the equation. -12 + 12 + 12x = 0 + 12 Combine like terms: -12 + 12 = 0 0 + 12x = 0 + 12 12x = 0 + 12 Combine like terms: 0 + 12 = 12 12x = 12 Divide each side by '12'. x = 1 Simplifying x = 1
| (4-x)+(8/4)=x+2 | | 35x+67x=20 | | -1/5x-1/7=20 | | 1/5x-1/7=20 | | 1/5x+1/7=77 | | 1/5x+1/7=23 | | 5(8y-5)=15y | | 1/5x+1/7=20 | | 1/5x+1/7=40 | | 1/2x1/7=40 | | -y+243=80 | | 282=-x+11 | | 68-v=206 | | -1/3x-1/5=20 | | 4y+20=8(y-2) | | -1/3x-5=20 | | 1/3x-5=20 | | 1/3-5=20 | | 3w+6/2=6w-4/7+10 | | -1/3+5=20 | | y+6=-1/10(x+12) | | -u+64=208 | | 4+18=8 | | 4/7x-5/3=3x+1/2 | | 6x+9y=200 | | x+3+x=35 | | x+4+x=78 | | 129=-2x+-5(2x-3) | | 129=-2x+5(2x-3) | | 6x-2=-12 | | x^2=5x-1 | | 6x-9=-17 |